Neutrophil-to-lymphocyte Ratio is Associated with LV Diastolic Dysfunction in the Overt Hyperthyroid Patients - Huan Zhang; Huan Zhang; Jiaoyue Zhang; Jiaoyue Zhang; Huan Li; Huan Li; Yaqiong Bi; Yaqiong Bi; Linfang Wang; Yuming Li; Yuming Li (Frontiers in Endocrinology, 2022)
BackgroundRecent studies have shown that the neutrophil-to-lymphocyte ratio (NLR) has gradually been identified as a more reliable marker of inflammation, with predictive value for the development of many diseases. However, its association with left ventricular (LV) diastolic dysfunction in overt hyperthyroid patients is unclear. Here, we aimed to explore the relationship between NLR and LV diastolic dysfunction in overt hyperthyroid patients.MethodsFor this study, we retrospected the consecutive medical files of 350 overt hyperthyroid patients. Their medical data and laboratory findings were recorded. According to the presence or absence of LV diastolic dysfunction, the patients with overt hyperthyroidism were divided into two groups. One group with LV diastolic dysfunction included 104 patients and another group with non-LV diastolic dysfunction included 246 patients. The NLR values between the two groups were compared, and the relationship between NLR levels and the prevalence of LV diastolic dysfunction was also explored.ResultsThe NLR value in LV diastolic dysfunction group in the overt hyperthyroid subjects was significantly higher than that in non-LV diastolic dysfunction group [1.100 (0.907-1.580) vs 1.000 (0.761-1.405), P=0.016]. The prevalence of LV diastolic dysfunction in Low- (NLR<0.879), Medium- (0.879< NLR<1.287), and High- (NLR >1.287) NLR level groups were 20.9%, 32.5% and 35.7% respectively. Moreover, increased NLR is associated with increased prevalence of LV diastolic dysfunction, and after adjustment for potential associated factors, NLR remained significantly associated with LV diastolic dysfunction. (OR = 11.753, 95%CI = 1.938-71.267, P = 0.007).ConclusionsOur findings demonstrated that the NLR was associated with LV diastolic dysfunction in the overt hyperthyroid patients, and the prevalence of LV diastolic dysfunction may be positively correlated with NLR levels.